Knowledge, Attitudes and Acceptance of Artificial Intelligence Assisted Antenatal Care Among Pregnant Women: A Cross-Sectional Study - Hemasa Gul, Huma Gul, Fatima Rehman, Tabassum Begum (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Artificial intelligence (AI) is increasingly being incorporated into antenatal care (ANC) systems globally, yet patient-level knowledge, attitudes, and acceptance in resource-limited settings such as Pakistan remain poorly characterized. Understanding these dimensions is essential for equitable and effective deployment of AI-based obstetric tools. Objective: To assess the level of knowledge, attitudes, and acceptance of AI-assisted antenatal care among pregnant women attending a tertiary care hospital in Mardan , Pakistan, and to identify sociodemographic determinants of these outcomes. Materials &Methods: A cross-sectional study was conducted at Department of Obstetrics and Gynecology, Mardan Medical Complex, Mardan, from January 2023 to June 2023. A total of 350 pregnant women were enrolled via systematic random sampling. A validated, structured questionnaire assessed three domains: knowledge (10 items), attitudes (8 items, Likert scale), and acceptance (6 items). Descriptive statistics, chi-square tests, and binary logistic regression were applied using SPSS v26. Significance was set at p < 0.05. Results:Mean age was 27.4 ± 5.1 years. Good knowledge of AI in healthcare was reported by 41.1% of participants. Positive attitudes toward AI-assisted ANC were expressed by 58.9%, and overall acceptance was 52.3%. Education level (OR 3.41, 95% CI 2.01–5.78), smartphone use (OR 2.87, 95% CI 1.65–4.99), and urban residence (OR 2.14, 95% CI 1.28–3.57) were significant independent predictors of AI acceptance. Key barriers included lack of AI familiarity (62.0%), trust concerns (54.6%), and privacy fears (49.7%). Conclusion: While over half of pregnant women showed positive attitudes toward AI-assisted ANC, acceptance was tempered by limited knowledge and specific trust barriers. Education-focused interventions and community engagement are necessary prerequisites for successful AI integration in maternal healthcare in Pakistan. Keywords: Artificial intelligence; antenatal care; pregnant women; knowledge; attitudes; acceptance; Pakistan; cross-sectional study